Technological Innovation on Corporate Sustainability: A Study of Airtel Nigeria - Olawale, Yinusa; Balogun, Ebenezer (Journal of Technology Management and Business, 2024)
When assessing the modern strength of business enterprises, the importance of organizational sustainability and the state of technical innovation are becoming increasingly important considerations. As a result, the research looks at how technological innovation affects organizational sustainability, specifically mentioning Airtel Network Nigeria in Ilorin, Kwara State. The study’s precise goals were to investigate how product innovation affects environmental sustainability, how process innovation affects economic sustainability, and how marketing innovation affects social sustainability. The study utilized a descriptive research design and employed a simple random sampling approach to randomly choose 103 employees from a population of 140 working at Airtel Network Nigeria in Ilorin, Kwara State. The sample size was determined using the Taro Yamane formula. A structured questionnaire was employed, and SmartPLS version 3 was utilized for analysis. PLS Algorithm and boostrapping were used to test hypotheses at the 0.05 significant level. The results showed that there is a significant positive correlation (R2 value of 42.8%) between environmental sustainability and product innovation; an even stronger correlation (R2 value of 32.6%) exists between economic sustainability and process innovation; and an even stronger correlation (R2 value of 40.5%) exists between social sustainability and marketing innovation. As a result, the study came to the conclusion that technological innovation has a very favorable effect on business sustainability. The study’s conclusions lead to a number of recommendations, one of which is that Airtel Network Nigeria and other telecom firms improve their product innovations to account for new goods or services in order to open up new markets or attract existing ones. Additionally, it recommends that they take into account innovative organizational methods, distinctive inputs that produce novel outputs, and a variety of organizational techniques.